Technology trends for 2023 : what O'Reilly learning platform usage tells us about where the industry is headed - Loukides, Michael Kosta (O'Reilly Media, Inc., 2023)
In this report, we look at the data generated by the O'Reilly online learning platform to discern trends in the technology industry: trends technology leaders need to follow.